2019
DOI: 10.1186/s11671-018-2834-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Titanium Dioxide Nanoparticles During Pregnancy Changed Maternal Gut Microbiota and Increased Blood Glucose of Rat

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) were used worldwide for decades, and pregnant women are unable to avoid exposing to them. Studies revealed that TiO2 NPs could kill many kinds of bacteria, but whether they would affect the composition of gut microbiota, especially during pregnancy, was seldom reported. And, what adverse effects may be brought to pregnant females was also unknown. In this study, we established the prenatal exposure model of rats to explore the effects of TiO2 NPs on gut microbiota. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
3
30
0
1
Order By: Relevance
“…Several studies showed mixed results on whether TiO 2 particles modified the composition of gut microbiota, [14,[22][23][24][25] and this discrepancy may be due to multiple factors such as the difference in characteristics of TiO 2 particles, oral doses, exposure time, exposure route, and animal models. In this study, fecal pellets were freshly collected from the colon at the time of sacrifice after 8 weeks of dietary treatments with TiO 2 particle.…”
Section: Tio 2 (E171) and Tio 2 Nps Altered The Composition Of Gut MImentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed mixed results on whether TiO 2 particles modified the composition of gut microbiota, [14,[22][23][24][25] and this discrepancy may be due to multiple factors such as the difference in characteristics of TiO 2 particles, oral doses, exposure time, exposure route, and animal models. In this study, fecal pellets were freshly collected from the colon at the time of sacrifice after 8 weeks of dietary treatments with TiO 2 particle.…”
Section: Tio 2 (E171) and Tio 2 Nps Altered The Composition Of Gut MImentioning
confidence: 99%
“…Some studies reported that TiO 2 NPs altered the compositions of gut microbiota and the bacterial metabolites; however, other studies reported no obvious disturbance of gut microbiota by TiO 2 NPs. [22][23][24][25] This discrepancy may be due to multiple factors such as the difference in characteristics of TiO 2 particles, oral doses, exposure time, exposure route, and animal models. It is notable that in most of these studies, TiO 2 was administered to rodents by oral gavage, a technique that has been shown to cause stress responses that may introduce a potential confounder in gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dietary TiO 2 dissolved in drinking water led to a decrease in mucus-related gene expression (i.e., Muc-2 ) and consequent impairment of the intestinal epithelial barrier, an increase in the antimicrobial peptide Defb3 gene expression, enhanced inflammatory response, and alteration of colonic crypt length [50]. A recent study by Mao and colleagues also investigated the impact of the exposure to TiO 2 particles in pregnant rats [51]. The authors reported a slight change in gut microbiota composition at gestation day 10 and 17 [51].…”
Section: Effects Of Food Additives On Gut Homeostasismentioning
confidence: 99%
“…A recent study by Mao and colleagues also investigated the impact of the exposure to TiO 2 particles in pregnant rats [51]. The authors reported a slight change in gut microbiota composition at gestation day 10 and 17 [51]. In addition, fasting blood glucose levels, together with the expression of diabetes mellitus-related genes, were increased in the exposed rats [51].…”
Section: Effects Of Food Additives On Gut Homeostasismentioning
confidence: 99%
“…Nanomaterials are widely used in production and life, and can easily be released and enter human body (Mao et al, 2019;Li et al, 2018). Consequently, the risk of human exposure to La 2 O 3 NPs has increased.…”
Section: Discussionmentioning
confidence: 99%